Crossing the Boundaries: Challenging Witches’ Stereotypical Marginalization in Multimedia Fiction and Nonfiction Texts - Rahayu, Nurhadianty; Pahlevi, Reza; Rahmawanti, Movi Riana (ENGLISH, 2024)
This study attempts to critically explore the representation of witches in two genres of text, i.e. popular animated movie Spirited Away and a historical essay published on history.com. Critical Discourse Analysis and Critical-feminist Approach to Marx’s ‘primitive accumulation’ are incorporated as the guiding framework in the data analysis process. Findings showcase that the representation of witches in animated movie highlights the criticism of capitalist disruption of Japanese gender roles as can be seen from the ambivalent characters of the movie’s main witch antagonist, Yubaba and her twin sister Zeniba. Furthermore, in the historical essay, findings portray that witches’ representation in historical article does not guarantee that they are free from marginalizing and stereotypical accusation. Even though the highlight is on the severe state-sponsored punishment and disciplining toward women’s body during the great witch hunt, the actors exerting power are made invisible, resulting in the perpetuation of unjust power balance within the society. Keywords: critical discourse analysis, critical feminist perspective, Marx’s primitive accumulation, witches’ representation